Precision of 30 guided implants in complex tumour situations. Issue 9 (November 2020) - Rostetter, C.; Abazi, J.; Gander, T.; Bredell, M.; Rücker, M.; Studer, S.; Zweifel, D.
Abstract: Implant born prosthetic rehabilitation of tumour patients can be difficult to perform. Challenges in treating such patients include disrupted anatomy with limited mouth opening due to previous ablative surgery as well as free-flaps or simple bone grafts, adjuvant therapy such as radiotherapy and, in general, poorer general health. Combining classical knowledge of ideal prosthesis placement and current virtual planning possibilities the positioning and in consequence the survival of dental implants can be optimised. Since prosthetic rehabilitation has a positive effect on the patients' quality of life and general health, we propose performing such surgeries as early as possible. All patients at our institution receiving pre-planned guided implant reconstruction and postoperative evaluation with Cone Beam Computed Tomography (CBCT) between 2015 and 2018 were evaluated for inclusion. Eight patients with a total of 30 implants met the inclusion criteria. The planned implant position was compared to the outcome position by fusing the two and deviations in entry-point position, apex-position, angular deviation and depth error were recorded. The mean (SD) discrepancy at entry-point was 2.28 (1.45) mm and 2.89 (1.53) mm at the apex, respectively. Mean (SD) angulation discrepancy was 9.5˚ (4.13˚) and the mean (SD) depth deviation was 1.52 (0.86) mm. Our results demonstrate the feasibility of pre-planned implant placement in challenging clinical situations and that only few concessions have to be made for precision.